A case study, Eric Hebborn, Rome Scholar 1959–61: The art and craft of forging a drawing. Issue 1 (1st April 2020) - Farthing, Stephen
An exploration of forgery and drawing that focuses on a twentieth-century practitioner, his art education, motivation and methodology, this critical article was inspired by a meeting that took place in a village near Rome during the autumn of 1976 between the author and Eric Hebborn (1934–96). Written some forty years later, this article has two goals; first to contribute to the debate that now circles the role of drawing within the contemporary fine art curriculum and then to question the nature of the biographical information Ruskin suggested was embedded in artists drawings. Hebborn, a skilful draftsman and award-winning alumnus of the Royal Academy Schools and British School at Rome is unusual in that he left no significant trace of himself as a contemporary artist. Using his memoire Drawn to Trouble, a once misattributed drawing The Lamentation of the Three Mary's and my recollections of the meeting, as entry points. This article portrays Hebborn as a victim of his art education, who in the final analysis was neither a fine artist nor copyist but instead an art school trained illusionist who openly admited to creating a modus operandi that was designed to trick experts into uttering false instruments.